Preparation of tin and tin sulfide alloy on carbons and graphene via chemical method for use as anodes in lithium-ion batteries - Waket T. (2017)
© 2016 Hanyang University. All rights reserved. Both tin (Sn) and sulfur (S) can act as hosts for lithium-ions and, therefore, Sn/C and SnS/C nanocomposites, prepared by the solution method, have the potential to be used as anodes in next-generation Li-ion batteries. One of the key factors in the design of promising anodes is the ability of their microstructure to accommodate the Li-insertion and de-insertion; hence, in the present study, various carbon types were employed, and the metal volume fractions (S and Sn) were varied in order to determine the most promising microstructures. Particularly, the types of carbons, which were considered in this study, were artificial graphite (AG), mesocarbonmicrobeads (MCMB), and graphene (GC). To prepare Sn/graphene composites, the amount of Sn was made to vary between 10 wt.% and 20 wt.%. As for the SnS/C materials, the Sn and S ratios were 10: 10 and 20: 20, and the types of carbon used were MCMB and AG. X-ray diffraction showed that Sn and SnS phases develop within graphite, and scanning electron microscopy revealed that these phases disperse well in graphite. Furthermore, transmission electron microscopy allowed for a better observation of the nanometer dimensions of the particle size in all the samples.